2021
DOI: 10.1302/2058-5241.6.200036
|View full text |Cite
|
Sign up to set email alerts
|

The management of displaced femoral neck fractures: a narrative review

Abstract: This article serves to review the existing clinical guidelines, and highlight the most recent medical and surgical recommendations, for the management of displaced femoral neck fractures (FNFs). It stresses the need for multi-disciplinary intervention to potentially improve mortality rates, limit adverse events and prevent further economic liability. Globally, the incidence of FNFs continues to rise as the general population ages and becomes more active. The annual number of FNFs is expected to exceed six mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…With the increase of life expectancy and development of medical technology, the incidence of this injury would rise year by year. It is estimated that the number of femoral neck fractures worldwide will over 3.9 million by 2050 1,2,4,5 . Owing to advanced age and concomitant underlying diseases (heart disease, diabetes mellitus, pulmonary disease, cerebrovascular disease) or limb immobilization after trauma, elderly patients with femoral neck fractures are prone to developing various complications after non-operative treatment, such as painful bed sores, deep vein thrombosis and depression, which would make the already poor prognosis further exacerbated 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of life expectancy and development of medical technology, the incidence of this injury would rise year by year. It is estimated that the number of femoral neck fractures worldwide will over 3.9 million by 2050 1,2,4,5 . Owing to advanced age and concomitant underlying diseases (heart disease, diabetes mellitus, pulmonary disease, cerebrovascular disease) or limb immobilization after trauma, elderly patients with femoral neck fractures are prone to developing various complications after non-operative treatment, such as painful bed sores, deep vein thrombosis and depression, which would make the already poor prognosis further exacerbated 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the mortality has been reported to range between 12 and 37% within 1 year of the injury [ 1 , 2 ]. With the aging of the general population and development of medical technology, the incidence of FNF will be increasing exponentially and the number has been estimated to be over 3.9 million worldwide by 2050 [ 3 , 4 ]. Therefore, it is imperative to identify and correct the modifiable risk factors contributing to mortality to explore the optimal personalized therapy [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of FNF depends not only on the classi cation of fractures, but also on age (7,8). In this study, patients with FNF were classi ed by new AO classi cation in different age groups.The purpose is to observe the proportion of new AO classi cation in FNF patients and provide reference for improving the upper age limit of IF treatment.…”
Section: Introductionmentioning
confidence: 99%